PENGARUH MODEL INKUIRI TERBIMBING BERBANTU ALAT PERAGA TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS V SD NEGERI 6 METRO TIMUR - Astikasari, Rissa; Gunawan , Ade; Rahman Aththibby , Arif (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Critical thinking skills are an important ability in science learning to help students understand concepts and solve problems systematically. However, learning that is still teacher-centered causes student involvement to be not optimal, plus abstract material on the human digestive system, so concrete and innovative learning media are needed. Therefore, a learning model is needed that is able to encourage students to be actively involved in the learning process. This study aims to determine the influence of the teaching aid-assisted guided inquiry model on the critical thinking ability of grade V students of SD Negeri 6 Metro Timur. The research uses a quantitative approach with quasi-experimental methods and Pretest-Posttest Control Group Design which was carried out in four meetings. The research subjects were the VA class as the experimental class (n=20) and the VB class as the control class (n=20). Data collection was conducted using pretest-posttest essay tests, observations, documentation, and instrument validation sheets. Data analysis used normality, homogeneity, independent sample t-test, and N-Gain tests. The results showed that the average pretest of the experimental class was 61.00 and the control was 55.50, while the experimental posttest of 82.00 was higher than the control of 72.75, with a difference of 9.25 points. The hypothesis test obtained a significance value of 0.002 < 0.05 so that H₀ was rejected and Hₐ was accepted. The N-Gain result of the experimental class was 0.5194 in the medium category, this was supported by the results of observation of student activities which increased from 85.5% in the good category in the second meeting to 90.00% in the very good category in the third meeting, showing that the learning process was active and conducive. It was concluded that the instruction-assisted guided inquiry model had an effect on the critical thinking skills of grade V students of SD Negeri 6 Metro Timur. Keywords: Guided inquiry model; teaching aids; critical thinking skills